2019
DOI: 10.1111/all.13783
|View full text |Cite
|
Sign up to set email alerts
|

Protease/antiprotease network in allergy: The role of Staphylococcus aureus protease‐like proteins

Abstract: Exogenous proteases derived from a variety of different species such as mites, fungi, and bacteria are constantly challenging the body-own homeostasis and increasing the complexity of the protease network. Allergens with protease activity can be a seasonal trigger for atopic diseases like allergic rhinitis or allergic asthma, and the constant exposure of perennial allergens can persistently aggravate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 112 publications
0
32
0
Order By: Relevance
“…Mutations in SERPINA3 leading to decreased α-1 anti-chymotrypsin serum levels were associated with the inflammatory lung diseases COPD and emphysema (43). Our study revealed a novel IL-33 regulation pathway of SERPINA3I inhibiting the IL-33 degrading mast cell chymase mMCP-4, which could be, with the equivalent human proteins, of general importance in allergic airway diseases (44). The human SERPINA3 is a known mast cell chymase inhibitor and could thus be relevant in IL-33 regulation (45).…”
Section: Discussionmentioning
confidence: 69%
“…Mutations in SERPINA3 leading to decreased α-1 anti-chymotrypsin serum levels were associated with the inflammatory lung diseases COPD and emphysema (43). Our study revealed a novel IL-33 regulation pathway of SERPINA3I inhibiting the IL-33 degrading mast cell chymase mMCP-4, which could be, with the equivalent human proteins, of general importance in allergic airway diseases (44). The human SERPINA3 is a known mast cell chymase inhibitor and could thus be relevant in IL-33 regulation (45).…”
Section: Discussionmentioning
confidence: 69%
“…IL‐33, one of the epithelium‐derived cytokines, plays an important role in type 2 immunity and functions as a protease sensor 56 . When exposed to allergen proteases, full‐length IL‐33 is cleaved, thereby activating the production of type 2 cytokines from ILC2s 57,58 . Mice that lack ILC2s but have Th2 cells display reduced Th2 cytokine and IgE levels, suggesting the importance of ILC2s in bridging innate and adaptive Th2 responses 59 .…”
Section: Tight Junction In Asthmamentioning
confidence: 99%
“…Although IL-33 is considered to play significant roles in NPs, the precise mechanism of the effect of IL-33 on eosinophils in NPs remains unclear. Proteases, which are contained in antigens, bacteria, and fungi, can induce IL-33 from epithelial cells and thus promote the Th2 response [46,47]. CRSwNP is associated with a high rate of nasal colonization by Staphylococcus aureus (S. aureus), which is associated with a severe disease phenotype, and S. aureus superantigens have been implicated in the pathogenesis of the Th2 response in the nasal mucosa as they induce the release of several cytokines such as IL-33 [36,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%